Conflict Resolution Through Consensus Building: Experiences from the Dayak Than Community of Sarawak, East Malaysia. - Jawan, Jayum (Universiti Putra Malaysia Press, 1996)
This paper examines conflict management and resolution, focusing specifically on the Dayak Iban society of Sarawak. It argues that conflicts can be substantially reduced if people are socialized to accept their respective roles in the socioeconomic and political structure of society. Conflicts among the communal Ibans are kept to a bare minimum because their sociocultural values promote harmonious interdependence among individuals. Those who transgress the community accepted norms of behaviour are quickly ostracized, reprimanded and made to feel greatly ashamed. Iban acceptance of their positions and roles within the social, economic and political structure of society has helped to maintain social harmony, economic justice and political stability. On a higher order, that is in Malaysian society, it is the realization of this sense of justice that made the NEP acceptable and successful in allocating the benefits of economic growth among the various ethnic groups in the country. In other words, each community according to its needs as seen by political leaders.